Model of the meteor trail coherent scattering - Kharchenko, Helen V. (Видавництво Львівської політехніки, 2012)
The model of the meteor radio channel based on the heuristic solving diffraction problem of the signal scattering by the ionized meteor trail, which allows to estimate coherent component of the time-varying scattered signal power is proposed.
Keywords: meteor trail; coherent scattering; electron density